Determination of the repulsive force of an electromagnet to provide the necessary clearance from the skip along the entire length of guides of electromagnetic lifting installation - B.A. Zhautikov; Riad Taha Al-Kasasbeh; A.A. Aikeyeva; A.R. Yerzhanov; A.K. Ayaganov (Қарағанды университетінің хабаршысы. Физика сериясы)
The finite element method was chosen as the method of modeling physical fields in electric machines. As the method of modeling physical fields in electric machines a finite element method was chosen. In the article a formula to express an imbalance between the energy stored in a magnetic field and the energy provided by the supplied electric current in this field, under given boundary conditions is used. It has been established that the experiment, planned by the Plakett-Berman matrices, makes it possible to obtain a multifactorial polynomial model of the «lifting vessel — conductor» system, which establishes a relationship between the values of static loads in this system and the operating conditions of the mine lifting systems. The proposed finite element method of considering a permanent magnet as a nonlinear source of a field makes it possible to abandon additional iterations when searching for working points of a magnet. The developed mathematical apparatus takes into account the distribution of magnetization over the cross section of a permanent magnet and identifies non-identical operating points of different magnet elements, which allows to calculate the fields created by the joint action of several current windings and permanent magnets with different orientations in nonlinear and anisotropic media with regard to their mutual influence.